Macular thickness in patients with refractive errors - A. A. Shpak; N. A. Morina; M. V. Korobkova (Российский офтальмологический журнал)
Purpose. To investigate the influence of the axial length of eyes on the average macular thickness and to develop a method for assessing this optical coherence tomography (OCT) parameter in patients with refractive errors. Material and methods. The study involved 132 patients (132 eyes) over 40; of these, 43 patients with hyperopia (axial length 20–22 mm), 38 patients with myopia (axial length 25–28 mm) and 51 healthy subjects with emmetropia with similar gender and age distribution (axial length 22.5–24.5 mm). OCT was performed on a Cirrus HD-OCT device (Carl Zeiss Meditec, USA). Results. The average macular thickness in the emmetropia group was 282.4 ± 10.2 (261–304) μm. In patients with myopia, it was on average 7 μm less (274.9 ± 10.5; from 250 to 296 μm, p = 0.005), and in patients with hyperopia it was almost 6 μm thicker (288.2 ± 12.5; from 258 to 313 μm, p = 0.032). In the emmetropia group, normative data for the average macular thickness were determined. For eyes with the axial length of 20–22 and 25–28 mm, corrections for calculating the average macular thickness in emmetropic eyes have been developed, allowing comparison with the normative data. Conclusion. The average macular thickness decreases with the increase of the axial length of the eye. An original technique for assessing the average macular thickness in patients with refractive errors, adapted to the Cirrus HD-OCT device, was developed. For this device, the normative database of healthy subjects with emmetropia aged of 41–80 years has been compiled.